2022
DOI: 10.3390/jpm12020186
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting the Success of Combined Orbital Decompression and Strabismus Surgery in Thyroid-Associated Orbitopathy

Abstract: To evaluate the safety and efficacy of orbital decompression combined with strabismus surgery in thyroid-associated orbitopathy (TAO) and identify factors leading to surgical success. A retrospective comparative case series was conducted on 52 patients who were treated with combined orbital decompression and strabismus surgery. Outcome measurements included perioperative Hertel exophthalmometry and strabismus measurements. Surgical success was defined as binocular single vision (BSV) in the primary and reading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Steiert et al examined visual parameters dependent on the orbital muscle volume fraction in a surgically treated GO cohort and suggested that the orbital muscle volume factor should be addressed during treatment decisions, while early orbital decompression should be considered particularly in decreased vision with orbital muscle enlargement [ 8 ]. In a way that is different to the traditional staged GO management order (decompression and then muscle surgery or lid surgery), Hsieh et al suggested that orbital decompression combined with strabismus surgery by experienced surgeons can achieve satisfactory outcomes in selected patients, especially for those with symmetry of orbitopathy, relatively simple strabismus and mild proptosis [ 9 ]. Choi et al further supported the use of customized orbital decompression surgery combined with eyelid or strabismus surgery in mild to moderate GO patients, as it had favorable cosmetic results comparable to those achieved through stepwise techniques [ 10 ].…”
mentioning
confidence: 99%
“…Steiert et al examined visual parameters dependent on the orbital muscle volume fraction in a surgically treated GO cohort and suggested that the orbital muscle volume factor should be addressed during treatment decisions, while early orbital decompression should be considered particularly in decreased vision with orbital muscle enlargement [ 8 ]. In a way that is different to the traditional staged GO management order (decompression and then muscle surgery or lid surgery), Hsieh et al suggested that orbital decompression combined with strabismus surgery by experienced surgeons can achieve satisfactory outcomes in selected patients, especially for those with symmetry of orbitopathy, relatively simple strabismus and mild proptosis [ 9 ]. Choi et al further supported the use of customized orbital decompression surgery combined with eyelid or strabismus surgery in mild to moderate GO patients, as it had favorable cosmetic results comparable to those achieved through stepwise techniques [ 10 ].…”
mentioning
confidence: 99%